Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
(-2,-2)
Step-by-step explanation:
use midpoint formula: (average of two x-values, average of two y-values)
(-7 + 3)/2 = -4/2 = -2
(1 + -5)/2 = -4/2 = -2
Answer:
[tex]let \: m \: be \: the \: mid \: point \\ m = (( \frac{( {x}^{1} + {x}^{o})}{2}) \: \: \: ( \frac{ ({y}^{1} + {y}^{o}) }{2} )) \\ m = (( \frac{( - 7 + 3)}{2} ) \: \: \: ( \frac{(1 + - 5)}{2} ) \\ m = ( \frac{ - 4}{2} \: \: \: \frac{ - 4}{2} ) \\ m = ( - 2 \: \: \: - 2) \\ mid \: point \: = \: \binom{ - 2}{ - 2} [/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.